Integrated cognitive behavioral intervention for functional tics (I-CBiT): case reports and treatment formulation - Maxwell, Amanda; Zouki, Jade-Jocelyne; Eapen, Valsamma (Frontiers in Pediatrics, 2023)
Introduction: The onset of the COVID-19 pandemic saw a global surge in functional tic-like behaviors (FTLBs). FTLBs are unique from primary tic disorders. They are thought to manifest through a complex interplay between environmental and personal factors, including the stress-arousal system, and are characterized by their sudden and explosive onset. Accordingly, common interventions for tic disorders show limited efficacy in this population. We present an Integrated Cognitive Behavioral Intervention for Functional Tics (I-CBiT) that uses an urge acceptance model to manage tics and related stress and anxiety.Methods: We describe the treatment outcomes of eight young people presenting with new and sudden onset FTLBs who underwent I-CBiT, which integrates traditional behavioral tic interventions with third-wave cognitive behavioral therapies. All cases completed the three-phase intervention involving core components of psychoeducation, exposure and response prevention with urge acceptance, sensory grounding strategies, and cognitive behavioral intervention targeting the stress-arousal system. Tic severity and impairment were assessed prior to treatment and at completion. Results: All cases showed a significant reduction in tic severity post I-CBiT and an improvement in overall daily living function. These cases highlight the role of urge acceptance in managing both tic urges and the underlying stress-arousal system to bring about long-term change.We demonstrated the efficacy of I-CBiT for managing FTLBs. Our findings illustrate the importance of treating underlying stress and anxiety in this population and, therefore, a need for greater interaction between multidisciplinary services in managing FTLBs to comprehensively cover the varied symptom presentations linked to thoughts, emotions, bodily sensations, and stress responses.